The Role of Nigerian Indigenous Languages in Covid-19 Discourse - Kenneth Ekezie Obiorah (Journal of Language and Health, 2021)
Nigerian Indigenous languages are quintessential to the modus operandi of communication in Nigeria. The indigenous languages are dominated by English language which is a lingua franca in Nigeria. Since the broke out of COVID-19 disease; a 'highly transmittable and pathogenic viral infection’ there have been several measures to contain the disease. The need to spread adequate information that will enhance the personal safety of Nigerians has led to the use of the indigenous languages in facilitating information sharing among indigenous people in Nigeria. Consequently, this study investigates the role of the Nigerian indigenous languages in the fight against COVID-19. Methodologically, data were collected through electronic media. Salawu’s model for indigenous language developmental communication was adopted for this study. The results of this study show that Nigerian indigenous languages are used in spreading COVID-19 preventive measures, media briefing on National television, health orientation and, medical research. This shows that the Nigerian indigenous languages which overtime has been dominated by English could be very significant at a critical time of medical delivery.